Hydroelectric Infrastructure and Potential Groundwater Contamination in the Brazilian Amazon: Altamira and the Belo Monte Dam. Issue 2 (3rd April 2019) - Gauthier, Cristina; Lin, Zihan; Peter, Brad G.; Moran, Emilio F.
Abstract : Heavy investments in hydroelectric development are occurring throughout the Amazon Basin, which holds 42.2 percent of Brazil's hydroelectric potential. The Belo Monte dam is the most recent and largest project in this region. The prevalence of septic systems in the Amazon, coupled with the widespread use of water wells and rising water table from filling the reservoir, create sanitation and health concerns for upstream communities. Using spatial analytical data and terrain analyses, we identify high-risk locations within the most densely populated neighborhoods in Altamira, Belo Monte's host city. The purpose of this research is to develop a heuristic for identifying areas susceptible to groundwater and well contamination in relation to existing and proposed hydroelectric projects. Altamira's city center persists as a high-risk location for contamination of wells because of its population density and relatively low elevation compared to other parts of the city. The methods, tools, and analyses presented in this article provide a framework that can be used to identify vulnerability to groundwater and drinking well contamination. The results presented here can guide implementation of public health and sanitation efforts in areas affected by large hydroelectric projects to avoid future water quality crises. Key Words: Belo Monte, groundwater contamination, hydroelectric infrastructure, risk assessment, spatial and terrain analyses.